Risk assessment of FMS and YBT on sports injuries in collegiate athletes - Xie, M.; Zhang, R.; Gong, Y. (International Journal of Sports Medicine, 2024)
This prospective cohort study investigated the predictive validity of the Functional Movement Screen (FMS) and Y Balance Test (YBT) for sports injuries in 458 collegiate athletes across various sports. Preseason screening using FMS and YBT was conducted, followed by injury data collection over the competitive season. Logistic regression analysis examined the relationship between screening scores and subsequent injury risk. Results indicated that lower composite FMS scores (=14) were associated with increased injury risk (OR=2.32; 95% CI: 1.54-3.48; p<0.001), as were YBT anterior reach asymmetries > 4 cm (OR=2.16; 95% CI: 1.43-3.26; p<0.001). The combination of both risk factors demonstrated the strongest association (OR=3.57; 95% CI: 2.18-5.83; p<0.001) when compared to individuals with FMS scores >14 and YBT asymmetry < 4 cm.The combination of low FMS scores and YBT asymmetries demonstrated the strongest predictive value. These findings underscore the value of the FMS and YBT as screening tools to identify collegiate athletes who may be at elevated risk for sports injuries, potentially guiding the implementation of targeted injury prevention strategies.